Topological Phenomenology of Space: Architecture as Roots of Infinity - Peter Magyar (Oz, 2014)
Ideas mature, but interestingly enough, they never get old! It is also notable how are they born. In my case, two elements brought them forward: one question and an admirably unique surrounding.